Performance of rapid test kits to assess household coverage of iodized salt. Issue 15 (11th May 2016) - Gorstein, Jonathan; van der Haar, Frits; Codling, Karen; Houston, Robin; Knowles, Jacky; Timmer, Arnold
Abstract: Objective: The main indicator adopted to track universal salt iodization has been the coverage of adequately iodized salt in households. Rapid test kits (RTK) have been included in household surveys to test the iodine content in salt. However, laboratory studies of their performance have concluded that RTK are reliable only to distinguish between the presence and absence of iodine in salt, but not to determine whether salt is adequately iodized. The aim of the current paper was to examine the performance of RTK under field conditions and to recommend their most appropriate use in household surveys. Design: Standard performance characteristics of the ability of RTK to detect the iodine content in salt at 0 mg/kg (salt with no iodine), 5 mg/kg (salt with any added iodine) and 15 mg/kg ('adequately' iodized salt) were calculated. Our analysis employed the agreement rate (AR) as a preferred metric of RTK performance. Setting/Subjects: Twenty-five data sets from eighteen population surveys which assessed household iodized salt by both the RTK and a quantitative method (i.e. titration or WYD Checker) were obtained from Asian (nineteen data sets), African (five) and European (one) countries. Results: In detecting iodine in salt at 0 mg/kg, the RTK had an AR>90 % in eight of twenty-three surveys, while eight surveys had an AR<80 %. When the RTK was used for detecting adequately iodized salt, the AR decreased significantly, with only one of fourteen surveys achieving an AR>90 %. Conclusions: The RTK is not suited for assessment of adequately iodized salt coverage. Quantitative assessment, such as by titration or WYD Checker, is necessary for estimates of adequately iodized salt coverage.